Stray Current Corrosion of Copper Sheathing and Keel Cooling Pipe of a 36’ Trawler - RAVINDRAN, K. (Fishery Technology, 1968)
The results of investigations into the cause of an accelerated corrosion of copper sheathing and keel cooling pipe of a 36’ wooden trawler are reported. The corrosion is attributed to the stray electric currents originating from the electrical wiring system. The sources of stray currents and the remedial measures have been suggested.